THE FLOUTING OF MAXIM IN THE SE7EN MOVIE SCRIPT - Ibrahim, Zulfah; Arifin, M. Bahri; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2018)
ABSTRACT This research focused on analyzing flouting of maxims that were flouted by the characters in the Se7en movie script and the motivation of the characters flouted the maxims. This research used qualitative research method. The data of the research were in the form of utterances that contained flouting of maxim. The data were collected by downloading the movie and the script, watching the movie, and collecting the data from the script. The data analysis was conducted by organizing the data into narration, analyzing the data, and drawing the conclusion. The results of the research showed what types of maxim were flouted in the movie and what motivation that led the characters to flout the maxims. There are four flouting of maxims in the Se7en movie script; they are maxim of quantity maxim of quality, maxim of relevance, and maxim of manner. Then, there are three motivations that influenced the characters flouted the maxims; they are competitive, collaborative, and conflictive. Keywords: flouting of maxim, Se7en movie ABSTRAK Penelitian ini difokuskan pada analisis pelanggaran maksim yang dilakukan oleh karakter dalam naskah film Se7en dan motivasi karakter melanggar maksim tersebut. Penelitian ini menggunakan metode penelitian kualitatif. Data penelitian berupa ujaran yang mengandung pelanggaran maksim. Data dikumpulkan dengan cara mengunduh film dan naskahnya, menonton film, dan mengumpulkan data dari naskah. Analisis data dilakukan dengan menyusun data dalam bentuk narasi, menganalisis data, dan menarik kesimpulan. Hasil penelitian menunjukkan jenis maksim apa saja yang dilanggar dalam film ini dan motivasi apa yang menyebabkan karakter tersebut melanggarnya. Ada empat maksim yang dilanggar dalam naskah film Se7en, yaitu maxim kuantitas, maksim kualitas, maksim relevansi, dan maksim cara. Lalu, ada tiga motivasi yang mempengaruhi karakter melanggar keempat maksim tersebut, yaitu kompetitif, kolaboratif, dan konfliktif. Kata kunci: pelanggaran maksim, film Se7en